Relations between criteria for somatic symptom disorder and quality of life in asylum seekers living in Germany - Giesebrecht, Julia; Grupp, Freyja; Reich, Hanna; Weise, Cornelia; Mewes, Ricarda (Journal of Psychosomatic Research, 2022)
Objective: Asylum seekers often suffer from medically unexplained symptoms that affect their quality of life (QoL). The present study is the first to investigate the extent to which somatic symptoms and the B criteria for the DSM-5 somatic symptom disorder (SSD) are associated with the QoL of asylum seekers living in Germany. Methods: In 144 asylum seekers, somatic symptoms (PHQ-15), B criteria for SSD, symptoms of posttraumatic stress (PDS), depressive symptoms (PHQ-9), post-migration living difficulties (PMLD), and QoL (EUROHIS) were assessed cross-sectionally. Multiple regressions in the total sample and in groups of somatic symptom severity (mild/moderate and severe) were conducted to examine the associations between somatic symptoms and B criteria with QoL. Results: Sleep problems and pain were the most frequently reported somatic symptoms. Sixteen (11%) participants met one B criterion, 24 (17%) met two, and 84 (58%) met all three criteria. QoL correlated negatively with somatic symptoms (r = −0.56, p < .001) and with the existence of at least one B criterion (r = −0.24, p < .001). In the total sample, stronger depressive and somatic symptoms were related to lower QoL (adjusted R2 = 0.53) while the B criteria were not. In persons with severe somatic symptom severity, the B criterion behavior was associated with lower QoL. Conclusion: In addition to stronger somatic and depressive symptoms, the psychological B criterion behavior seems to play an important role in the lower QoL of asylum seekers with severe somatic symptoms.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Asylum seekers; B criteria; Quality of life; Somatic symptom disorder